A Major QTL, Which Is Co-located with cly1, and Two Minor QTLs Are Associated with Glume Opening Angle in Barley (Hordeum vulgare L.) - Zhang, XinZhong; Guo, BaoJian; Lan, GuoFang; Li, HongTao; Lin, Shen; Ma, Jun; Lv, Chao; Xu, RuGen (Frontiers in Plant Science, 2016)
Cleistogamous and chasmogamous are two opposing phenomena for flowering in barley. Cleistogamy limits the rate of outcrossing, and increases the cost of producing hybrid barley seeds. Selecting chasmogamous lines with a large glume opening angle is essential for the utilization of barley heterosis. In the current study, 247 DH lines derived from a cross between Yangnongpi7 and Yang0187 were used to identify and validate QTLs associated with the glume opening angle in different environments using SSR markers. Three QTLs associated with barley glume opening angle were mapped on chromosomes 2H and 7H. The major QTL QGOA-2H-2 was mapped on chromosome 2H with the flanking markers of KDH and GBM1498, explaining 63.92% of the phenotypic variation. The marker KDH was developed from the gene Cly1, the candidate gene for QGOA-2H-2. This new marker can be used to identify barley chasmogamous lines with a large glume opening angle. The two minor QTLs were validated at all three locations across two seasons after removing DH lines carrying the candidate gene Cly1 of QGOA-2H-2.